Small interfering RNA: Discovery, pharmacology and clinical development—An introductory review - Ranasinghe, Priyanga; Addison, Melisande L.; Dear, James W.; Webb, David J. (British journal of pharmacology, 2023)
Post‐transcriptional gene silencing targets and degrades mRNA transcripts, silencing the expression of specific genes. RNA interference technology, using synthetic structurally well‐defined short double‐stranded RNA (small interfering RNA [siRNA]), has advanced rapidly in recent years. This introductory review describes the utility of siRNA, by exploring the underpinning biology, pharmacology, recent advances and clinical developments, alongside potential limitations and ongoing challenges. Mediated by the RNA‐induced silencing complex, siRNAs bind to specific complementary mRNAs, which are subsequently degraded. siRNA therapy offers advantages over other therapeutic approaches, including ability of specifically designed siRNAs to potentially target any mRNA and improved patient adherence through infrequent administration associated with a very long duration of action. Key pharmacokinetic and pharmacodynamic challenges include targeted administration, poor tissue penetration, nuclease inactivation, rapid renal elimination, immune activation and off‐target effects. These have been overcome by chemical modification of siRNA and/or by utilising a range of delivery systems, increasing bioavailability and stability to allow successful clinical translation. Patisiran (hereditary transthyretin‐mediated amyloidosis) was the first licensed siRNA, followed by givosiran (acute hepatic porphyria), lumasiran (primary hyperoxaluria type 1) and inclisiran (familial hypercholesterolaemia), which all use N ‐acetylgalactosamine (GalNAc) linkage for effective liver‐directed delivery. Others are currently under development for indications varying from rare genetic diseases to common chronic non‐communicable diseases (hypertension, cancer). Technological advances are paving the way for broader clinical use. Ongoing challenges remain in targeting organs beyond the liver and reaching special sites (e.g., brain). By overcoming these barriers, siRNA therapy has the potential to substantially widen its therapeutic impact.